A study on dehairing of vicuña fiber: evaluation of yields and quality characteristics that impact on its transformation and textile added value - Sacchero, Diego Mariano; Lamas, Hugo Eduardo; Maurino, Maria Julia; Galfione, Luciano (Taylor and Francis, 2024)
Dehairing is a key process in the textile transformation of double-coated animal fibers such as vicuña fleeces. The process consists in the mechanical separation of the coarse fibers (and additionally other foreign particles) from the fine fibers of high textile value. In Argentina, the degree of mastery of the techniques and capabilities required for the efficient processing of vicuña fiber is still unclear. This paper reports study results on the vicuña fiber dehairing process by applying the protocol currently used in a mill. The yield, diameter, and content of coarse and fine fiber fractions, and fiber lengths before and after dehairing were compared. The results indicate that the separation efficiency of fine fibers from the initial raw material was high, whereas that in the by-products was low. The dehairing process reduced the fiber length considerably and the coarse fiber content by 50%, leading to a comfort factor of 99%.